2019
DOI: 10.13005/ojc/350229
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Depressor Additives Application Efficiency for Asphaltene-Resin-Paraffin Deposits Inhibition and Stripping in Petroleum Storage Tanks

Abstract: Possibility of heated petroleum application with various additives addition as solvents for asphaltene-resin-paraffin deposits was analyzed. An object of this investigation was chosen petroleum selected from tank farm of the Kazakhstan oil refinery and samples of bottom sediments (ARPD) formed during storage in tanks. Deposits type in line with ARPD classification was identified. Additives impact on petroleum capacity in relation to ARPD was investigated. The most effective additives to inhibiting and removing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It should be noted that the intensity of the absorption bands characteristic of alkanes (at 728 cm −1 ) and alkenes (at 693 cm −1 ) is significantly increased in the sample of hydrocarbon with a solvent the addition of EVA. We found that an increase in the content of EVA from 5% to 10% did not have a notable effect on fluidity or viscosity, because vinyl acetate groups react with paraffins and asphaltenes [1]. As such, we introduced EVA-25 into Karazhanbas oil together with the solvent that we synthesized.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It should be noted that the intensity of the absorption bands characteristic of alkanes (at 728 cm −1 ) and alkenes (at 693 cm −1 ) is significantly increased in the sample of hydrocarbon with a solvent the addition of EVA. We found that an increase in the content of EVA from 5% to 10% did not have a notable effect on fluidity or viscosity, because vinyl acetate groups react with paraffins and asphaltenes [1]. As such, we introduced EVA-25 into Karazhanbas oil together with the solvent that we synthesized.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, the developed composition lowered the pour point of oil and reduced the precipitation of paraffin crystals. We found that an increase in the content of EVA from 5% to 10% did not have a notable effect on fluidity or viscosity, because vinyl acetate groups react with paraffins and asphaltenes [1]. As such, we introduced EVA-25 into Karazhanbas oil together with the solvent that we synthesized.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation